Analysis of pre-service teachers’ knowledge about the entrepreneurial competence: a case study of a Spanish university - Arruti, Arantza; Benitez, Estibaliz; Paños-Castro, Jessica (Frontiers in Psychology, 2023)
Introduction This research is based on the role played by the entrepreneurial competence (EC), entrepreneurial education (EE) and teachers in the social, economic and cultural development of a society. The general objective of the study is to analyze the level of knowledge pre-service, those who are studying, or have recently studied, the Bachelor’s Degree in Primary Education at the University of Deusto (Spain) (DPEUD) have about the EC. Methods A questionnaire, based on EntreComp Framework, underwent expert validation and was applied to a sample of 304 students. Results The data showed that 25% of the respondents believed that EE was related to educating through entrepreneurship; more than 45% did not know about EntreComp and EntreCompEdu, whereas only three participants were aware of how to use them; and more than 10% of the pre-service teachers did not consider assessing the CE. Discussion These results lead to the conclusion that there is a need for EE to form part of the different national teacher training strategies; and for policy makers to include EE in the different educational frameworks, laws and decrees. In addition, it can be concluded that social, cultural and economic value can be created through entrepreneurial actions; that EC should be assessed; and that teachers should motivate students to share and implement entrepreneurial ideas and actions.